Tackling outdated misconceptions: Pathways to establish fruitful dialogues between Behavior Analysis and Social Psychology (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
The behavior analyst’s interest for social and cultural issues turns the necessity of establishing dialogues with other areas of knowledge, such as Social Psychology, Sociology and Anthropology, into a priority. That being the case, to explore what is being written about behaviorism in the literature of those areas can be seen as a first step towards the dialogue. After all, if our goal is to establish contact, maybe is prudent to start by investigating what they “think of us”. Our goal in this article was to evaluate how behaviorism is presented in Social Psychology books, one of the areas we think is worth establishing contact with. We analyzed 11 books considered main references on the field and found out that most comments were unfavorable misconceptions about behaviorism. We found in Lane (1981/2006, 1984), however, a well-informed argument pointing to the incompleteness of the behavior analysis of social behavior. We ended the article by considering possible strategies to tackle the misconceptions about behaviorism in our endeavor to establish dialogue with other areas interested in social and cultural processes.
Keywords: Behavior Analysis; Social Psychology; Behaviorism; Social and Cultural Processes; Misconceptions